а) 4/11
( 6*4 / 6*11)(при сокращении)
Пошаговое объяснение:
х⁴-7²-18 =0 представим как (х²-9)(х²+2)=0
х²-9=0 х²+2=0
х²=9 х²=-2 не соответствует
х=+-3
-3*(-2)=6 3*(-2)=-6
ИЛИ
представим х²=а
а²-7а-18=0
D=(-7)²-4*(-18)=49+72=121=11²
х₁=(7+11)/2=9
х₂=(7-11)/2=-2 не соответствует
подставляем
х²=9
х=√9
х=+-3
-3*(-2)=6 3*(-2)=-6
не понял
2х²+2х-9х-9=х²+3х-3х-9
2х²+2х-9х-9-х²-3х+3х+9=0
х²-7х=0
х(х-7)=0
х=0 х-7=0
х₁=0 х₂=7
(84·8·4)/(14·2·24·11) = (6·1·2)/(1·1·3·11) = (2·2)/(1·11) = 4/11
ответ: а) 4/11.
Пояснения:
84 и 14 сокращаем на 14
8 и 24 сокращаем на 8
4 и 2 сокращаем на 2
- - - - - - -
6 и 3 сокращаем на 3